The effect of industrial diversification and geographic diversification on the practice of earnings management (An Empirical Study On Manufacturing Companies Listed On Indonesian Stock Exchange Year 2011-2014) - Dahlia Dahlia; Basri Hasan (Proceedings of AICS - Social Sciences, 2016)
This research is conducted to address the prevalent issues regarding the effect of industrial diversification and geographic diversification either partially or simultaneously on the practice of earnings management. By utilizing purposive sampling techniques on the secondary data, the total of 80 sample studies are drawn from manufacturing companies listed on Indonesian Stock Exchange for the period of 2011-2014. Multiple linear regression analysis provided by SPSS 21.0 is also employed to test the hypothesis constructed within this research. The result of the multiple linear regression analysis presents evidence that industrial diversification and geographic diversification simultaneously have a significant effect on the practice of earnings management. Alongside, it also affirms that partially, industrial diversification and geographic diversification respectively has a significance effect on the practice of earnings management. These findings help to provide scholarly evidence on the implication of diversification strategies on the practice of earnings management to help financial statement users (investor, creditor, stakeholder, etc.), accounting standard setter, and regulators to assess the pervasiveness of earnings management within the company.